THE EFFECT OF FAMILY-BASED EDUCATION PROGRAMS ON INCREASING FINANCIAL RESOURCES WITH HANDMADE PRODUCTION FROM WASTE BATIK FABRIC - Endang Lifchatullaillah; Mohammad Fanani (Jurnal Ekonomi, 2023)
Handmade is the process of making product objects that are processed by hand. The handmade business is identified with the label of high creativity, so it has a sale value and is in great demand by consumers. The results of this craft are limited and original, so lovers of anti-mainstream products will prefer the work of the handmade business. This study aims to analyze the effect of family-based educational programs on family behavior and increase in financial resources with handmade production from batik cloth waste. The design used in this study was a pre-experimental design, namely the one group pre-post test design. The sample in this study was taken on a probability/random basis using the cluster random sampling technique. The analysis was carried out using univariate and bivariate methods